Massachusetts State House, Beacon Street, 1864 - Unknown (Tufts Archival Research Center, 2005)
Street-level view looking northwest toward the state capitol building from the corner of Park and Beacon Streets. Mount Vernon Street is on the right. A fountain is on the lawn, statutes of Horace Mann and Daniel Webster flank the main stairs. An ironwork fence surrounds the perimeter of the lawn. In the foreground is a street light at the corner of Beacon Street. Architect was Charles Bulfinch. 10 x 13 1/4 Photographs